Enhancing learners' problem solving performance in mathematics: A cognitive load perspective - Joseph J. Dhlamini (Lectito Journals, 2016)
This paper reports on a pilot study that investigated the effect of implementing a context-based problem solving instruction (CBPSI) to enhance the problem solving performance of high school mathematics learners. Primarily, the pilot study aimed: (1) to evaluate the efficiency of data collection instruments; and, (2) to test the efficacy of CBPSI in relation to learners' problem solving performance. In this paper CBPSI refers to a teaching approach in which everyday problem solving knowledge and practices are uncovered when learners are exposed to tasks that give meaning to their everyday experiences. Given that the design of a pilot study lacked the inclusion of a control group, it is reasonable to conclude that the current design embraced elements of a pre-experimental research approach in which a one-group pre-test post-test design was followed. Participants consisted of a convenient sample of 57 Grade 10 learners who performed poorly in mathematics problem solving. The results of the study informed various conceptual and methodological revisions to strengthen the design of the main study, however, this paper reports only the effect of CBPSI on participants' problem solving performance. The post-intervention achievement test suggested that CBPSI was effective in substantially accelerating learners' problem solving performance (p<0.05). Using a cognitive load theory, it is possible to explain aspects of growth in learners' problem solving performance in relation to the conceptual notion of human cognitive architecture.